Impact of merger on bank performance - Goet, Joginder (Management Dynamics, 2021)
In this study, accounting ratios has been used to analyze the financial performance of Citizens Bank International Ltd. in Nepal before and after merger. I have analyzed their financial statements for six years by using various ratios. In spite of certain limitations, accounting ratios are still considered as a convenient and reliable analytical tool. Ratio analysis, being a time-tested technique, is most frequently employed in all financial decision-making processes. The results show that the financial performance of CBI Ltd. in the areas of profitability and stability has been most satisfactory after merger. It means that merger deal success to improve the financial performance of the bank.